Questioni di vita Introduzione alla bioetica - Manzini, Arianna; Vitiello, Liberio (FrancoAngeli, 2019)
If bioethics has established itself for the past fifty years, it is because it has been able to intercept the questions of an ethical nature raised by the irruption of technology in the world of life. When genetic engineering makes it possible to manipulate the innermost basis of living beings, the question of responsibility for interventions that touch such an important and complex structure must be taken seriously. Faced with the expansion of the technical potential of medicine, the question arises of how to protect life and health, but with respect for the dignity of the person. When fundamental experiences such as being born and dying are subjected to increasing medicalization, we are all challenged to maintain a hold on the human dimension of these events. The aim of this Introduction to bioethics is to educate these questions in the most honest and rigorous way possible, highlighting their specifically ethical aspects together with the anthropological implications, and giving account of the most significant orientations that are confronted on them.